KONTRAK SOSIAL: WAKAF, ZAKAT, INFAQ DAN SHADAQAH - Yenni Samri Juliati (Universitas Islam Negeri Sumatera Utara, 2015)
Islam is a doctrine concerned with the welfare of his people, other forms of assistance to improve welfare distribution in the compulsory alms in the form of teaching, so that the Muslims who are well off are required to provide in accordance with the family fortune treasure half of ratio / Shariah conditions set for the less able. While the distribution of assets from the original invitation keridhoaan realized with the recommendation to do waqaf, infaq and Sadaqah.